GAMBARAN PENGETAHUAN IBU MENYUSUI TENTANG RESIKO PEMBERIAN MAKANAN TAMBAHAN PADA BAYI USIA 0-6 BULAN DI KELURAHAN KOTA SIANTAR LORONG KAYUARA KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL TAHUN 2021 - Lubis, nurkholidah (Jurnal Kesehatan Ilmiah Aufa Royhan, 2021)
ABSTRACT Supplementary feeding means providing food other than breast milk where breast milk is a natural food for babies and must be given without additional food until the age of 6 months, but the fact is that there are still many mothers who give food to babies aged under 0-6 months. This descriptive study aims to describe the knowledge of breastfeeding mothers about the risk of giving additional food to infants aged 0-6 months in Siantar Lorong Kayuara Village, Panyabungan District, Mandailing Natal Regency. Collecting data using primary data obtained from the results of filling out questionnaires by respondents. The sampling technique in this study was using the total sampling technique. The results of the study were that the majority of respondents had less knowledge, namely 18 respondents (51.4%). Based on the age of the majority of good knowledge aged 25-35, namely 11 respondents (50%). Based on education, the majority have less knowledge with high school education, namely 11 respondents (52.3%). Based on the occupation, the majority have less knowledge of the work of farmers, namely 8 respondents (57.1%). Based on parity, the majority have less knowledge with parity Multipara, namely 7 respondents (63.6%). Based on the sources of information, the majority have less knowledge than sources of information from electronic media and health workers, each of which is 7 respondents (58.3%). From the results of this study, it can be concluded that the knowledge of breastfeeding mothers about the risk of giving additional food to infants aged 0-6 months is lacking, for that it is hoped that health workers can increase counseling for breastfeeding mothers about all matters related to supplementary feeding.